Hydrocephaly management in patients with tumors in the posterior fossa. - Osmany Morales Sabina; José Ramón Tejera del Valle; Juan Francisco Piñeiro Martí; Omar López Arbolay (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Introduction: Preoperative hydrocephalus is reported in about 80 % of posterior fossa tumor patients and in 15-40% of cases postoperative treatment for persistent or progressive hydrocephalus is required. There is no consensus on the way hydrocephalus should be managed before, during, and after PF surgery. Objective: To determine the presence of hidrocephalia in the tumors of the PF and the therapeutic focus in our means. Methods: We report a descriptive, retrospective study of 10 adult patients with posterior fossa mass lesions and obstructive hydrocephalus who were managed medically for compensate intracranial hypertension plus observation and were operated through posterior fossa craniectomy and tumor excision as unique method of surgical treatment. Results: In all 10 cases clinical improvement was obtained immediately after medical treatment. Circulation of cerebrospinal fluid (CSF) was totally restored only by tumor excision in 9 patients. The other case had progression of hydrocephalus after surgery and a ventriculoperitoneal shunt was inserted. Radiological normal sized ventricles was obtained between one and two months of surgery Conclusions: Surgical elimination of CFS circulation obstacle helped by medical treatment for lower intracranial pressure should be considered as a safe option in adult patients, reserving endoscopic ventriculostomy and shunt insertion for cases with persistent or progressive hydrocephalus after treatment. Prospective multicenters randomized trials are needed to obtain stronger evidences.